Enhancing Teacher Performance Through Millennial Teacher Characteristics, Work Culture, and Person-Job Fit Mediated by Employee Engagement - Rachman, Azhariah; Sunarno, Sunarno; Saputra, Nanda; Judijanto, Loso; Nurhidin, Edi; Zamroni, M Afif (Nazhruna: Jurnal Pendidikan Islam, 2024)
Teachers are the key to the success of a nation in improving the quality of life of its people in the future. This research aims to find research gaps with previous research which makes four main points to be used as questions in this research, namely 1. Analyzing the characteristics of millennial employees, work culture, and personal job fit towards lecturer competence. 2. Analyzing millennial employees, work culture, and personal job fit on lecturer performance 3. Analyzing lecturer competency on lecturer performance 4. Analyzing the extent to which the role of lecturer competence mediates the characteristics of millennial employees, work culture, and personal job fit on lecturer performance. This research method uses quantitative research with an explanatory research approach. The number of samples in this study was 105 selected using the census method. To test the hypothesis in this study, structural equation model analysis techniques were used. The results of this research show that the findings show that efforts to increase Employee Engagement through millennial employee characteristics, work culture, and personal job Fit have the potential to make a positive contribution to improving employee performance. The following recommendations are for teachers to increase employee engagement, so teachers need to be focused and stimulated to encourage teachers to be more innovative in their work so they can improve teacher performance and for future researchers to evaluate the variables of this research on different populations and increase the population size.